Team Marvel receiving 1st place (first place) award for their prototype firefighter uniform design - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Team Marvel and Alan Fletcher.
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards